The Quest for Teachers of the Right Stamp as Prerequisite to Progress of Female Education in Eastern Bengal: The Partition Interlude - Nayeem, Asha Islam (Arts Faculty Journal, 2012)
When the nineteenth century came to its glorious end, in Bengal, the storm surrounding the question of womens education had settled in favor of progress. Conditions for the spread of female education, however, were still precarious, to say the very least. The three chief deterrents to the spread of female education, as recorded in official documents, were: (a) the custom of early marriage, after which girls dropped out of school and more often than not lapsed into ignorance; (b) the system of purdah, the social custom which prevented grown up girls from venturing out of the house to attend school; and, (c) the lack of female teachers (Report on Public Instruction, 1899-1900). DOI: http://dx.doi.org/10.3329/afj.v4i0.12932 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.53-74